Pengembangan Media Pop Up Book Suku Kata Tema Binatang untuk Meningkatkan Kemampuan Membaca Permulaan Anak Usia 5-6 Tahun - Yana Hauri; Haryanto Haryanto; Akhmad Fikri Rosyadi (CV. Alim's Publishing, 2026)
Early reading skills are visual activities that involve the process of translating written symbols into sounds. Children's early reading skills will be developed through learning media that are appropriate to the child's developmental stage. This study aims to identify the need for developing pop-up syllabic learning media to improve the early reading skills of children aged 5-6 years. This study uses a descriptive qualitative approach. Identification of needs is based on three aspects, namely learning media, learning strategies, and analysis of early reading skills. The subjects of this study consisted of 3 teachers and the principal of Kindergarten Al Falah Islamic Kindergarten, Pelita Doktora Kindergarten, and Rizani Putra Kindergarten. Data collection techniques used were interviews and documentation. Data analysis was carried out using the Miles Huberman Technique which includes the stages of data collection, data reduction, data display, and drawing conclusions/verification. The results of the study indicate that identification of needs is based on three aspects, namely learning media, learning strategies and analysis of early reading skills. In identifying learning media, it is necessary to develop interesting learning media. Then, in identifying learning strategies, a fun strategy is needed to achieve children's beginning reading skills, and is child-centered. Meanwhile, the analysis of children's beginning reading skills revealed the need for pop-up book media to improve children's relevant beginning reading skills.